Oxidative Stress and Its Biomarkers in Cardiovascular Diseases - Julija Valaitienė; Agnė Laučytė-Cibulskienė (Artery Research)
Abstract Background Cardiovascular diseases (CVDs) are the most common cause of death worldwide. CVDs share heterogeneous pathophysiologic mechanisms, one of which includes increased oxidative stress. Main Body Surplus levels of reactive oxygen species induce damage to cellular macromolecules such as DNA, proteins, and lipids. Increased reactive oxygen species result in decreased nitric oxide availability, vasoconstriction, and the development of procoagulant and proinflammatory states in blood vessels. Conclusion Improved knowledge of biomolecular processes triggered by oxidative stress has helped develop tools for assessing oxidative stress markers and applying them in clinical settings. Nevertheless, some research gaps should be filled, specifically by defining the most clinically relevant biomarkers for oxidative stress with high sensitivity and specificity for CVD.